Degradation study of phenolic compounds in waste water of gas stations using filamentous fungi (Aspergillus Flavus) - Zanin, Evandro; Silva, Iara Elisa Cardoso da; Lopes, Toni Jefferson; Cancelier, Adriano; Costelli, Murilo Cesar; Silva, Adriano da (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
Several compounds are synthesized and industrially produced, where in most cases, are hardly degraded or recycled in the way they are. A large portion of contamination process can be attributed to phenolic compounds found with different concentrations in wastewater from gas stations. In this study, we attempted to isolate and identify filamentous fungi capable of phenolic compounds degradation and evaluate, using experimental design techniques, the effects of temperature and pH on degradation yield of phenolic compounds. Aspergillus flavus fungi lineage was isolated in this study. Results showed that the fungi lineage was little affected by changes in pH and showed better performance at 25°C and pH 8, when 6.7 ppm of phenol was degraded.